2017
DOI: 10.1002/ppul.23651
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant administration via a thin endotracheal catheter during spontaneous breathing in preterm infants

Abstract: To systematically review the clinical outcomes of surfactant administration via a thin endotracheal catheter during spontaneous breathing compared with conventional administration involving tracheal intubation, mechanical ventilation (MV), and tracheal extubation, in preterm infants. PubMed, EMBASE, and the Cochrane Library were searched to identify relevant clinical trials. Data were analyzed using the Cochrane Collaboration methods. Primary outcome measures included the incidence of MV and bronchopulmonary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, a large cohort study found LISA to be associated with a significant reduction in invasive ventilation (12% versus 18%, P = 0.001), reduced postnatal steroid use (2.5% versus 7%, P < 0.001), BPD (12% versus 18%, P = 0.001) and BPD or death (14% versus 21%, P < 0.001) 40 . Furthermore, Wu et al analyzed the results from selected trials using LISA and validated the beneficial aspects of the thin-catheter strategy in terms of decreased requirement of MV and, consequently, a reduction in BPD incidence 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large cohort study found LISA to be associated with a significant reduction in invasive ventilation (12% versus 18%, P = 0.001), reduced postnatal steroid use (2.5% versus 7%, P < 0.001), BPD (12% versus 18%, P = 0.001) and BPD or death (14% versus 21%, P < 0.001) 40 . Furthermore, Wu et al analyzed the results from selected trials using LISA and validated the beneficial aspects of the thin-catheter strategy in terms of decreased requirement of MV and, consequently, a reduction in BPD incidence 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose sedation was associated with an increased comfort score, but the need for transient non-invasive ventilation was increased [ 42 ]. A catheter inserted too deep can result in unilateral surfactant deposition leading to pneumothorax and PIE secondary to unilateral lung hyperinflation, but this has not been seen as a major problem in studies to date [ 43 ]. There are other possible adverse effects of LISA.…”
Section: Insurementioning
confidence: 99%
“…It would not make much sense to combine studies that have different comparators in a meta-analysis. A recently published systematic review by Wu et al addresses the outcomes of surfactant administration in a minimally invasive way (via thin endotracheal catheter) to spontaneously breathing infants (14). In this review, four studies are included for the outcome of requiring mechanical ventilation within the first 72 h of life (15)(16)(17)(18).…”
Section: Heterogeneity In Included Populations Interventions Contromentioning
confidence: 99%